Informal Competition and Innovation in Southeast Asian Countries: Examining the Moderating Influence of Gender - Doan, Thi Ngoc Thuy; Chang, Chia-Hua (Journal of Social Economics Research, 2022)
This study investigates the impact of informal competition on the innovation of Southeast Asian firms and the moderating role of female management in the informal competition–innovation nexus. In the Southeast Asian context, the informal sector employs around 78% of the working population, which is higher than the world average of 61% and the Asia-Pacific average of 68%. The analysis is based on firm-level data collected by the World Bank for eight Southeast Asian countries in 2015–2016. The quantitative analysis was conducted with the use of the multilevel mixed-effects logistic regression method to address the hierarchical/multilevel problem. Additionally, the potential endogeneity problem was taken into account with the use of the propensity score matching technique. The findings show that informal competition induces firms to increase their product and process innovations. Furthermore, female management is important in leveraging the positive effects of informal competition on innovation.